Advances in the oral microbiota and rapid detection of oral infectious diseases - Xiao, Xuan; Liu, Shangfeng; Deng, Hua; Song, Yuhan; Zhang, Liang; Song, Zhifeng (Frontiers in Microbiology, 2023)
Several studies have shown that the dysregulation of the oral microbiota plays a crucial role in human health conditions, such as dental caries, periodontal disease, oral cancer, other oral infectious diseases, cardiovascular diseases, diabetes, bacteremia, and low birth weight. The use of traditional detection methods in conjunction with rapidly advancing molecular techniques in the diagnosis of harmful oral microorganisms has expanded our understanding of the diversity, location, and function of the microbiota associated with health and disease. This review aimed to highlight the latest knowledge in this field, including microbial colonization; the most modern detection methods; and interactions in disease progression. The next decade may achieve the rapid diagnosis and precise treatment of harmful oral microorganisms.